2005
DOI: 10.1103/physrevb.72.195342
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of the quasi-one-dimensional reconstructions induced by Eu adsorption on a Si(111) surface

Abstract: The surface structures of the ͑quasi-͒one-dimensional reconstructions induced by the adsorption of Eu on Si͑111͒ have been investigated by low-energy electron diffraction ͑LEED͒ and high-resolution core-level photoelectron spectroscopy. Different phases were observed in LEED depending on the Eu coverage. The lowest coverage phase has a ͑3 ϫ 2͒ periodicity, and the highest coverage phase has a ͑2 ϫ 1͒ one. Of the intermediate phases, the LEED pattern of the so-called ͑5 ϫ 1͒ surface indicates that this surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
(90 reference statements)
2
7
0
Order By: Relevance
“…The model also explains the HCC-͑3 ϫ 2͒ structures with 1/6 ML alkali-earth and rare-earth metals. [23][24][25][26][27][28][29] A comparison between the ͑3 ϫ n͒ ͑n =1,2͒ structures induced by monovalent and divalent metals leads to a simple rule that the optimal coverage of the adsorbed metal atoms is determined to fill the dangling bonds of the honeycomb chains. On the other hand, two probable adsorption sites of the metal atoms are proposed; the H 3 and T 4 sites, both being threefold symmetry sites on the ͑111͒ substrate of the diamond structure.…”
Section: Introductionmentioning
confidence: 99%
“…The model also explains the HCC-͑3 ϫ 2͒ structures with 1/6 ML alkali-earth and rare-earth metals. [23][24][25][26][27][28][29] A comparison between the ͑3 ϫ n͒ ͑n =1,2͒ structures induced by monovalent and divalent metals leads to a simple rule that the optimal coverage of the adsorbed metal atoms is determined to fill the dangling bonds of the honeycomb chains. On the other hand, two probable adsorption sites of the metal atoms are proposed; the H 3 and T 4 sites, both being threefold symmetry sites on the ͑111͒ substrate of the diamond structure.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier Sakamoto et al 10,11 concluded that the ͑5 ϫ 2͒ and ͑5 ϫ 4͒ reconstructions are stable while ͑5 ϫ 1͒ is not. Using our theoretical method we can examine the relative stabilities of these reconstructions.…”
Section: Relative Stabilities Of Reconstructionsmentioning
confidence: 80%
“…The 1/3 ML coverage of Ca, however, has been reported to produce a clear ͑5 ϫ 4͒ reconstruction. From an analysis of core-level photoemission spectra, Sakamoto et al 10 proposed two structural models for the Eu/ Si͑111͒-͑5 ϫ 4͒ surface with a coverage of 1/3 ML. In one model, called the H 3 model, each ͑5 ϫ 4͒ surface unit mesh contains four Eu atoms adsorbed on the T 4 site and two Eu atoms on the H 3 site.…”
Section: Caõ Si(111)-(5 ã 4)mentioning
confidence: 99%
See 2 more Smart Citations